The Influence of Choice Feminism on Women's and Men's Attitudes towards Name Changing at Marriage: An Analysis of Online Comments on UK Social Media. (3rd July 2018) - Peters, Eleanor
Abstract : Analysis of name changing choices women have undertaken in English-speaking Western countries such as the USA and in the UK indicate that there are various predictors of whether women change their name at marriage or not, one of which is whether they identify as a feminist. This research examines the views of women and men on the issue of choice in name changing at marriage on a UK-based internet forum, Mumsnet, and in the British newspaper The Guardian online and explores whether identification with feminism has an influence on traditional name changing choices performed by women and men. The paper concludes that societal change is necessary to accommodate genuine free choice in name changing at marriage.